THE IMPACT OF THE COVID-19 PANDEMIC ON THE MANAGEMENT OF THE SUMATRAN TIGER (panthera tigris sumatrae pocock) IN CONSERVATION INSTITUTIONS FOR THE PUBLIC INTEREST (CASE STUDY AT TAMAN SAFARI INDONESIA CISARUA BOGOR AND RAGUNAN WILDLIFE PARK JAKARTA) - Herdiana Herdiana; Sata Yoshida Srie Rahayu; Rita Retnowati (Journal of Science Innovare, 2022)
The World Health Organization (WHO) as a world health institution declared COVID-19 as a global pandemic on March 11, 2020 and Indonesia officially announced a confirmed case of COVID-19 infection on March 2, 2020. One of the tourist attractions affected by COVID-19 is the Conservation in the Public Interest such as safari parks, zoos and animal parks. This study aims to: analyze the management of the Sumatran Tiger in the Indonesian Safari Park Cisarua Bogor and the Ragunan Wildlife Park during the COVID-19 pandemic, analyze the steps to minimize the impact of the COVID-19 pandemic on the management of the Sumatran Tiger at the Indonesian Safari Park Cisarua Bogor and the Ragunan Wildlife Park. as well as formulating a strategy for managing the Sumatran Tiger in the face of a disease pandemic at the Taman Safari Indonesia Cisarua Bogor and the Ragunan Wildlife Park. The research method used is descriptive research method. The source of research data comes from primary data sources, namely the management of the Indonesian Safari Park Conservation Agency Cisarua Bogor and Ragunan Wildlife Park and secondary data sources obtained from literature studies. The data taken are the management of Sumatran tigers at the Cisarua Bogor Indonesian Safari Park and Ragunan Wildlife Park and the types of use of the Sumatran tiger in the Cisarua Bogor Indonesian Safari Park and Ragunan Wildlife Park. Field observations were carried out to photograph and directly collect data on the condition of the Indonesian Safari Park Conservation Institute, Cisarua Bogor and Ragunan Wildlife Park, as well as the management of the Sumatran Tiger which includes aspects of management, manpower handling animals, and utilization and documentation studies. Processing of data from observations, interviews and documentation studies using descriptive qualitative analysis, and SWOT analysis. Based on the results of the study, that the operational management of the Sumatran Tiger at Taman Safari Indonesia Cisarua Bogor and the Ragunan Wildlife Park runs in accordance with the rules of animal management applied at the General Conservation Institute even though the COVID-19 pandemic has affected the income generated from visitor entrance tickets, especially for the park. Safari Indonesia Cisarua Bogor. The implication of this research is to minimize the impact of the COVID-19 pandemic on the operational management and protection of Sumatran tigers in the General Conservation Institute, the government together with the Indonesian Zoo Association and the managers of the General Conservation Institute need to immediately draw up an emergency plan for animal management, especially the Sumatran tiger, while maintaining based on aspects of animal welfare and compiling Standard Operating Procedures to prevent the spread of COVID-19.